Effects of body weight on some blood plasma parameters of pigs from the Alentejano breed - Martins J.M.; Neves J.; Freitas A.B.; Nunes J. (5. International Symposium on the Mediterranean Pig, 2007)
This work has evaluated the influence of body weight (BW) on some plasma parameters of Alentejano pigs. Thirty castrated Alentejano pigs (~35 kg BW) were allocated in individual pens and fed a commercial diet (0.85 x ad libitum). The pigs were slaughtered in groups (n=5) with an average BW of 42.2, 70.9, 80.2, 90.1, 100.5, and 110.2 kg. Plasma samples obtained at slaughter were analysed. Glucose and triacylglycerol levels decreased (P=0.05) with increasing BW, suggesting that during growth Alentejano pigs increased the use of glucose and triacylglycerols as energy and substrate for fat synthesis and deposition. Total cholesterol increased (P=0.05) with BW, due to an increase (P=0.05) in the low-density lipoprotein (LDL) cholesterol level, following the trends reported in ageing mammals. The Alentejano pig, with a high lipogenic activity, could be a valuable model for studies of the cholesterol metabolism.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)